Procedura zarządzania ryzykiem zintegrowanym - wyniki badań - Sus-Januchowska, Aleksandra (Procedure of management integrated risk - results of empirical research, 2005)
Empirical research related to integrated risk and integrated risk management was conducted in 2004. The main goals of that research was to answer two questions: 1) can risk be an integrator of board activity in three areas: quality, environmental and work safety management? 2) could early identification and estimates of integrated risk result in the elimination of potential risk, through making a preventive system, also called an early warning system? Part of the research which shows how to organize operations in case of risk - that is, identifying it, making quality estimates, and choosing an integrated risk strategy - are introduced in the present article.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 342-349